CLIFF-GRADS Science Collaboration Series 2020 - Thematic student session: Soil Systems - Chirinda, Ngonidzashe; Turek, Maria Eliza; Silva Santos, Erick Rodrigo da; Amenchwi, Amahnui George; dos Santos, Ricardo Cesário; Mlambo, Antony; Shefine, Bethel Geremew; Okolo, Chukwuebuka Christopher (Global Research Alliance on Agricultural Greenhouse Gases (GRA) & CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), 2020)
Featured Speaker: Dr. Ngonidzashe Chirinda, Soil and Climate Change Scientist, Mohammed VI Polytechnic University, Morocco.